Curative Surgical Treatment of Cerebral Palsy- A Case Presentation (Journal of Monno Medical College, 2023)
There was no cure for Cerebral Palsy (CP) previously. However, there are many treatment options that may help to improve daily functioning of a child suffering from CP. But these options failed to prevent early death of the patients. New curable treatment era has started for CP patients with bilateral cranioplasty and duraplasty. This was the second case of the case series of CP treated by bilateral cranioplasty and duraplasty with very good outcomes. During operation of this patient, after removing cranial bones by craniotomy, found no dural pulsation. It is indicative of raised intracranial pressure. After duraplasty, brain pulsation was found very nicely, which indicates that intracranial pressure became normal. In early childhood, brain grows with the dural growth simultaneously. But dura is adherent with the skull bones. Premature closure of sutures and with thickening of skull bones result in small intracranial volume which does not allow the brain to grow according to age. So, brain atrophy causes widened fissures and widened sulci with brain parenchymal tissue loss as evidenced in CT scan of brain or MRI. In this case, we made adequate rooming for brain by doing cranioplasty and duraplasty and got excellent results.J Monno Med Coll June 2022;8(2): 57-60